Carcass characteristics and yield of the primary cuts of lambs fed broom millet (Sorghum bicolor var. Technicum, jav) - Estrada, A.; D?vila, H.; Herrera, Rafael Segundo; Robles, J. C.; La O, Orestes; Castro, Beatriz I.; Portillo, J. J.; R?os, F. G.; Contreras, G. (Cuban Journal of Agricultural Science, 2012)
The effect of broom millet (Sorghum bicolor var. Technicum, jav), entire or ground was studied in the carcass characteristics and primary cuts in 40 pelibuey ovines (Dorper x Pelibuey), of 31.55 ? 6.02 kg of live weight during 42 d. Seventy five percent of broom millet entire was substituted by that ground. A completely random design with two treatments and four replicates was used. A feeding test with 40 animals receiving integral diets was conducted. The inclusion of entire broom millet did not influence significantly on the final live weight, weight of the hot carcass, rib eye area, width of the dorsal and renal-pelvic fat, weight of the digestive viscera and weight of the primary cuts. However, the carcass yield decreased (P < 0.05) (56.01 vs. 52.94 %) as well as the percentage of empty body (84.74 vs. 81.62 %) and increased (P < 0.05) the percentage of filled viscera (26.39 vs. 23.94 %), weight of the gastrointestinal content (6.84 vs. 5.71 kg) and percentage of the gastrointestinal content (18.38 vs. 15.26 %). It is concluded that the inclusion of entire broom millet in the feeding of lambs diminishes the carcass yield, without affecting its characteristics, weight of the primary cuts and their relation. Key words: carcass characteristics, cut, broom millet, Pelibuey sheep.